A fresh look at angiogenesis in juvenile idiopathic arthritis - Świdrowska-Jaros, Joanna (Cent Eur J Immunol, 2018)
Angiogenesis is the complex process of creating new capillaries from preexisting blood vessels due to hypoxemia, injury or inflammation of the tissues. Numerous cytokines and cell mediators have been identified to induce and stimulate angiogenesis, but vascular endothelial growth factor (VEGF) is a key regulator. The role of proangiogenic factors in the pathogenesis of chronic arthritis is currently a subject of intensive investigations in adult patients with rheumatoid arthritis (RA) and, to a limited extent, in children with juvenile idiopathic arthritis (JIA). Recent studies has shown a significant correlation between proangiogenic marker concentrations and the severity of inflammation in either RA or JIA patients. The serum neovascularization markers correlate with the power Doppler ultrasound image of the inflamed joint and hypertrophic synovium, which may be connected with the disease activity. The aim of this paper is to describe the state of the art on the important role of angiogenesis in adult and childhood rheumatoid arthritis.